2011
DOI: 10.1111/j.1423-0410.2011.01468.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro storage characteristics of platelet concentrates suspended in 70% SSP+TM additive solution versus plasma over a 14‐day storage period

Abstract: Platelets suspended in a medium of 70:30 SSP+™ to plasma ratio performed at least as well as platelets in 100% autologous plasma for up to 10 days of storage. Further, results are suggestive of an apoptosis-like process being involved in the platelet storage lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…PS exposure increased only minimally during the normal shelf-life of PCs but by day 12, the exposure had increased significantly. Others have also shown an increase in PS exposure during storage, but to various degrees [6,16,18,30], the consequences of these apoptotic features during storage are largely unknown. Our results are in accordance with the results by Leytin et al [32] that platelet activation is triggered before exposure of apoptotic features and our results support the hypothesis that apoptosis is triggered beyond the current shelf-life [1,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PS exposure increased only minimally during the normal shelf-life of PCs but by day 12, the exposure had increased significantly. Others have also shown an increase in PS exposure during storage, but to various degrees [6,16,18,30], the consequences of these apoptotic features during storage are largely unknown. Our results are in accordance with the results by Leytin et al [32] that platelet activation is triggered before exposure of apoptotic features and our results support the hypothesis that apoptosis is triggered beyond the current shelf-life [1,30].…”
Section: Discussionmentioning
confidence: 99%
“…Platelet detection was based on anti-CD41a-PE fluorescence and forward scatter properties [17] and P-selectin or PS exposure presented as percentage of PECy5+ or FITC+ platelets, respectively, with the marker in the negative control samples set to 1-2% positive platelets [18].…”
Section: Expression Of Gpib P-selectin and Phosphatidylserine (Ps) Omentioning
confidence: 99%
“…PASs supplemented with approximately 30% to 35% plasma are capable of supporting in vitro PLT quality during normal liquid storage for at least 10 days . Reconstituting frozen PLTs in SSP+ has been investigated; however, supplementation with 50% plasma was required to obtain reasonable postthaw recovery .…”
mentioning
confidence: 99%
“…PASs supplemented with approximately 30% to 35% plasma are capable of supporting in vitro PLT quality during normal liquid storage for at least 10 days. 13,14 Reconstituting frozen PLTs in SSP+ has been investigated; however, supplementation with 50% plasma was required to obtain reasonable postthaw recovery. 15 The development of new-generation glucose-containing additives, such as PAS-G, Intersol-G, and PAS-5, support a reduction in residual plasma while maintaining the in vitro quality of liquid-stored PLTs to a level equivalent to PLTs stored in 100% plasma.…”
mentioning
confidence: 99%
“…However, most studies suggest that the use of additive solutions does not make a big difference with the use of plasma. Saunders et al reported that the percentage of activated platelet was similar between platelets resuspended in additive solutions and platelets resuspended in 100% autologous plasma for up to 10 days of storage [37]. In the same way, Gyöngyössy et al founded that platelet concentrates resuspended in additive solution with glucose showed similar characteristics in activation (CD62P), morphology, pH glucose metabolism and swirl, when they were compared to platelets in plasma [38].…”
Section: Discussionmentioning
confidence: 92%